A REVISION OF GENUS VATICA L. (DIPTEROCARPACEAE) IN BORNEO II:VATICA ABANG-ZOHARII, A NEW SPECIES FROM SARAWAK - Meekiong, Kalu; Latiff, A; Yahud, W. (Forestry Department Peninsular Malaysia, 2021)
A new species Vatica abang-zoharii Meekiong, Latiff & Yahud is described and illustrated. This new species is quite similar to V. elliptica but can be readily distinguished by its bark greyish brown, small lenticels scattered along the stem, low buttress and shorter petioles that turned black when dry. V. abang-zoharii displays unequal fruit calyx (three long and two short) thus belongs to sect. Sunaptea. With the discovery of this new species, the number of species of Vatica in Sarawak has now increased to 34.